Handover Scenarios for Mobile WiMAX and Wireless LAN Heterogeneous Network - NMAED Wirastuti; CCW Emehel (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents proposed handover scenarios for a heterogeneous network comprising mobile worldwide interoperability for Microwave Access and Wireless Local Area Network segments. Homogenous handover scenarios for a mobile WiMAX network are also considered to allow a comparative analysis. A mobile node supporting voice traffic is analysed, when operating in a half-cell overlap coverage scenario, for both pedestrian and vehicular speeds. All proposed handover scenarios are assessed and validated through system-level Media Independent Handover network simulations. Results for both homogenous and heterogeneous handover show that the handover delay and jitter are within the acceptable values published by the WiMAX Forum. For heterogeneous handover, the packet loss is negligible for all cases; however, there were significant occurrences of packet loss in throughput for homogenous handover at vehicular speeds. This is due to the fact that the implementation of an adaptive channel scanning algorithm to allocate scanning intervals can limit communication disruptions.